Probable claws - Brown, Rita Mae; Brown, Sneaky Pie, 1982- (Brown, Rita Mae. Mrs. Murphy mystery., 2018)
"Rita Mae Brown and her feline co-author Sneaky Pie Brown return with a new tale in their bestselling Mrs. Murphy series, as mysteries past and present converge in Albemarle County, Virginia. Mary Minor "Harry" Haristeen and her friends and animal companions pursue the threads of a mystery dating back to Virginia's post-Revolutionary past, when their 18th-century predecessors struggled with the challenges of the fledgling country. In the present day, Harry's new friendship with Marvella Lawson, doyenne of the Richmond art world, leads her to rediscover her own creative passions--and reveals evidence of an all too contemporary crime"--